2007
DOI: 10.1093/cercor/bhl160
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory-Specific Activity in Auditory Cortex: Potential Correlates of Sequential Processing and Maintenance

Abstract: Working memory (WM) tasks involve several interrelated processes during which past information must be transiently maintained, recalled, and compared with test items according to previously instructed rules. It is not clear whether the rule-specific comparisons of perceptual with memorized items are only performed in previously identified frontal and parietal WM areas or whether these areas orchestrate such comparisons by feedback to sensory cortex. We tested the latter hypothesis by focusing on auditory corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
40
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 67 publications
10
40
1
Order By: Relevance
“…For example, it is possible that those primary areas not only represent modalityspecific sensory information while a stimulus is presented, but also are able to maintain some of that information ''on line'' during the working memory period of a discrimination task, and perhaps even participate in the subsequent decision-making steps. For instance, there are several reports suggesting that primary sensory cortices are involved to some degree in working memory tasks (34)(35)(36). Furthermore, a recent study has shown that, in addition to representing acoustic features, responses in A1 and R auditory fields may serve to encode some cognitive task elements associated with auditory processing (29), which also seems consistent with the idea that auditory cortex becomes selective to other sensory modalities when these are associated with auditory processing during action selection (29).…”
Section: Discussionsupporting
confidence: 63%
“…For example, it is possible that those primary areas not only represent modalityspecific sensory information while a stimulus is presented, but also are able to maintain some of that information ''on line'' during the working memory period of a discrimination task, and perhaps even participate in the subsequent decision-making steps. For instance, there are several reports suggesting that primary sensory cortices are involved to some degree in working memory tasks (34)(35)(36). Furthermore, a recent study has shown that, in addition to representing acoustic features, responses in A1 and R auditory fields may serve to encode some cognitive task elements associated with auditory processing (29), which also seems consistent with the idea that auditory cortex becomes selective to other sensory modalities when these are associated with auditory processing during action selection (29).…”
Section: Discussionsupporting
confidence: 63%
“…But because only right AC seems able to explicitly distinguish a rising from a falling continuous FM, it must be assumed that an interaction with other parts of cortex that serve the behavioral consequences of this task is selectively established with right AC. This idea of flexible task-dependent interactions in cortex is much supported by human fMRI results (44,45) and by anatomical evidence. Unlike subcortical auditory stations where processing steps can be explained by convergent and divergent ascending inputs, even primary AC receives Ͼ50% of its inputs from other cortical areas including many nonauditory fields (60).…”
Section: Discussionmentioning
confidence: 79%
“…In human functional (f)MRI experiments, we found that the categorization of direction of FM stimuli produced dominant blood-oxygen leveldependent (BOLD) activation of right AC, but categorization of their duration resulted in activation of left AC (44). Moreover, a matching-to-sample task with the same FM stimuli in serial comparisons generated dominant left AC activations (45). Similarly, in a ''streaming'' task, where the selective segmental comparison of stimuli is crucial, BOLD activation was lateralized to the left AC (46).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Learning-related plasticity in A1 develops in a wide range of tasks, including habituation (Condon &Weinberger, 1991), classical reward (Kisley & Gerstein, 2001) and aversive (Bakin & Weinberger, 1990) conditioning, instrumental reward (Blake et al, 2002) and avoidance (Bakin, South, & Weinberger, 1996) learning, category learning (Ohl, Scheich, & Freeman, 2001), long-term training in perceptual discrimination learning (Recanzone, Schreiner, & Merzenich, 1993), working memory (Brechmann et al, 2007;Sakurai, 1994), reference memory (Sakurai, 1994) and motor planning (Villa, Tetko, Hyland, & Najem, 1999). A dominant finding has been that sounds which acquire behavioral significance receive "favored" processing, e.g., as indexed by specific increased magnitude of response and CSdirected tuning shifts.…”
Section: Introductionmentioning
confidence: 99%